Perlindungan Adat atas Wanprestasi Nafkah di Kota Solok sebagai Penegakan Hukum Berbasis Komunitas untuk Menambal Celah Keadilan - Musfa Hengki; Sri Yunarti; Farida Arianti; Zulkifli Zulkifli; Nofialdi Nofialdi (IDRIS Darulfunun Institute, 2026)
This study aims to analyze legal protection for ex-wives due to default on post-divorce maintenance in Solok City using a local wisdom approach. The main issue raised is the weak execution of court decisions regarding iddah, mut'ah, and madliyah maintenance, and how Minangkabau customary mechanisms can address this gap. The research method used was qualitative field research. Data were collected through observation, review of decision documents, and in-depth interviews with ex-wives, Religious Court judges, and traditional leaders such as Ninik Mamak and Bundo Kanduang. The results indicate that the implementation of post-divorce maintenance in Solok City is not optimal. Many ex-wives do not file maintenance claims in order to expedite the divorce process, while existing decisions are often not executed by ex-husbands. Formal legal protection is available through instruments such as withholding of divorce certificates, but local wisdom-based protection through mediation by Ninik Mamak and the role of Bundo Kanduang has not been fully utilized. Key inhibiting factors include the ex-husband's low economic status, lack of legal awareness, and limited asset evidence during court proceedings. Conversely, the strength of formal legal structures and the customary values of